Phytochemical-mediated modulation of signaling pathways: A promising avenue for drug discovery - Jibon Kumar Paul; Mahir Azmal; ANM Shah Newaz Been Haque; Omar Faruk Talukder; Meghla Meem; Ajit Ghosh (Advances in Redox Research)
Phytochemicals are bioactive compounds derived from plants, renowned for their therapeutic potential. This study explores their pivotal roles in therapy and drug development, focusing on their interactions with crucial Signaling pathways and biological processes. Phytochemicals such as curcumin from turmeric, resveratrol from grapes, and epigallocatechin gallate (EGCG) from green tea, exert their effects primarily by modulating key pathways like PI3K/AKT, MAPK-ERK, Wnt, and Hedgehog, which are integral to cellular functions and disease progression. Phytochemicals like curcumin demonstrate potent anticancer activities by inhibiting proteins involved in cell proliferation, inducing apoptosis, and suppressing angiogenesis. Phytochemicals such as resveratrol also exhibit anti-inflammatory properties by targeting cytokine production and oxidative stress pathways, thereby alleviating chronic inflammatory conditions implicated in various diseases. Their (eg. EGCG's) antioxidant capabilities help neutralize free radicals and reduce oxidative damage, contributing to cellular health and longevity. Moreover, phytochemicals play a pivotal role in metabolic disorders such as diabetes and obesity by regulating glucose metabolism, lipid profiles, and insulin sensitivity. They also show promise in neurodegenerative diseases by protecting neuronal cells, enhancing cognitive functions, and potentially mitigating neuroinflammation and oxidative stress. For instance, berberine, an alkaloid found in several plants, shows promise in regulating glucose levels and improving insulin sensitivity. Additionally, ginsenosides from ginseng are known to protect neuronal cells, enhance cognitive functions, and potentially mitigate neuroinflammation and oxidative stress in neurodegenerative diseases. Despite their promising therapeutic benefits, challenges remain, particularly in ensuring bioavailability and standardization of phytochemical extracts for clinical use. Advances in screening techniques and formulation strategies aim to enhance their efficacy and integration into modern therapeutic approaches. Their multifaceted roles in modulating cellular processes underscore their importance as potential alternatives or complements to traditional pharmacotherapies, driving innovation in drug development and personalized medicine.